Comparison of digital and visual tooth shade selection. Issue 2 (13th February 2023) - Abu‐Hossin, Sabrin; Onbasi, Yonca; Berger, Lara; Troll, Florian; Adler, Werner; Wichmann, Manfred; Matta, Ragai‐Edward
Abstract: Objective: In dental restorations, color determination is very important for achieving esthetic results. The aim of this study was to compare visual shade selection using digital methods and to assess the repeatability of the utilized intraoral scanners. Materials and methods: In 31 probands, tooth color was determined on teeth 11, 13, and 16. Shade selection was performed visually by a dentist and digitally using Trios 3 and Cerec Omnicam. Three measurements were performed to determine the repeatability of intraoral scanners. Fleiss' κ was used for statistical evaluation of the repeatability and Cohen's κ was used for comparison of methods. Results: The visual method showed only slight agreement with Trios 3 (Cohen's κ : 0.198) and Cerec Omnicam (Cohen's κ : 0.115). Moderate agreement was found between Trios 3 and Cerec Omnicam (Cohen's κ : 0.452). In terms of repeatability, Trios 3 scored higher overall than Cerec Omnicam (Fleiss' κ : 0.612 vs. 0.474). Conclusion: Intraoral scanners can facilitate the workflow in clinical practice. They are a good supplement for color determination, but should additionally be confirmed by the visual method. Clinical significance: The use of digital instruments is increasingly being preferred over conventional treatments. Therefore, it is essential to continuously improve the accuracy of intraoral scanners for color selection in order to offer an alternative to visual methods.